Pemberdayaan Masyarakat pada Sektor Parawisata dalam Upaya Percepatan Pemulihan Ekonomi - Frahmawati Bumulo; Sri Endang Saleh (Mopolayio : Jurnal Pengabdian Ekonomi, 2021)
Community Empowerment in the Tourism Sector in Efforts Acceleration of Economic Recovery in Dambalo Village As an effort to grow the economy which is currently slumped as a result of the covid 19 pandemic. He people of Dambalo Village have various livelihoods from self-employed fishermen, farmers and some are civil servants and construction workers, all of which aim to help the family economy. and almost 60% are creative and micro business actors. Here fore, we are interested in providing creative ideas in the tourism sector, where in this village there is a pretty good tourist attraction to be developed, namely the Botudidingga tourism object, as for the tourism objects in this village that have existed since a few years ago which are located on the coast which has its own uniqueness, because to go to this place the tourists seem to go on a trip to the mountains, the vast expanse of sea surrounded by mangroves and has a courtyard to the middle of the sea makes Botudidingga tourism object the maldeves of North Gorontalo. To further beautify and attract tourists, the thematic village community service students create interesting photo spots with materials taken in the village of Dambalo itself